Utilization of Android-Based Animation Video Learning Media to Increase Student Motivation for Learning Arabic in Higher Education - Shidqi, Muhammad Husni; Salam, Muhammad Yusuf; Batubara, Anitia Anggreini; Mudinillah, Adam; Levan's, Olivia (Institut Agama Islam Negeri Palangka Raya, 2024)
Carrying out the duties of an educator in the 21st century, particularly at the higher education level, requires the ability to develop educational skills in conjunction with advanced technological products in the form of digital applications to support learning activities. One such application is the Android-based animation video application, Plotagon Story. This study aims to determine the level of student motivation in learning Arabic using the Plotagon application. The research method used is qualitative, utilizing questionnaires distributed to respondents. The results of this study indicate that Android-based animation videos using the Plotagon Story application can provide motivation and enthusiasm for students in learning Arabic. The implications of these findings are that the Plotagon application can increase student motivation in learning Arabic and enhance their creativity and ability to meet the challenges of mastering technology-based learning media integrated with good language proficiency.